A STUDY ON THE EFFECTIVENESS OF THE INSTAGRAM APP IN DEVELOPING VOCABULARY OF STUDENTS - Kaldarova, Aissulu; Vasquez, Marco; Utemuratova, Alima (Scientific Journal of Astana IT University, 2025)
This study examines the effectiveness of Instagram as a tool to improve vocabulary learning among students, focusing solely on quantitative analysis. As social media platforms become integral to students' daily routines, Instagram’s visual and interactive features may offer unique benefits for vocabulary acquisition. The aim of this research is to determine whether Instagram enhances vocabulary retention and engagement compared to traditional learning methods. A quantitative method was applied, involving 60 students divided into four groups of 15 each. These groups engaged with vocabulary lessons delivered through Instagram posts, stories, and interactive quizzes over a twelve-week period. Pre/posttests were used to measure vocabulary retention, providing a clear comparison of learning outcomes.The data analysis revealed a statistically significant improvement in vocabulary retention across all groups, indicating that Instagram can serve as an effective supplementary tool for vocabulary development. Additionally, students who interacted more frequently with Instagram content demonstrated better performance, suggesting that consistent social media engagement positively influences learning outcomes. The study highlights the importance of visually appealing and context-rich content in improving memorization and understanding of new vocabulary. Interactive elements, such as polls and quizzes, were especially effective in fostering active learning and sustaining student interest. The findings suggest that Instagram’s accessibility and familiarity can help bridge gaps in traditional teaching methods, and it makes learning more relatable and enjoyable for students. Teachers may find it valuable to explore similar platforms to create engaging digital learning environments. This research underscores the need to integrate modern technology into education to maximize student participation and outcomes.